The impact of increase in the domestic petroleum prices of cost production in the agricultural and agro-based sectors - Saari, Mohd Yusof; Radam, Alias; Abdullah, Amin Mahir (Universiti Malaysia Serawak, 2008)
By using an input-output model, the present paper examines the impacts of increase in the domestic petroleum prices on cost production in the Malaysian agricultural and agro-based sectors. This study simulates the different scenarios of the petroleum price changes on sectoral cost production, which comprises of domestic materials cost, imports and labor. The simulation results indicated that the agricultural sector particularly fishing, forestry and logging products, as well as oil palm primary products industries are mostly affected by the increase of the domestic petroleum price. These industries are significantly affected by domestic petroleum price increase because they consume large amount of petroleum products as intermediate inputs in their production process.